The best at it - Pancholy, Maulik, 1974- (Balzer + Bray, 2019)
Twelve-year-old Rahul Kapoor heads into seventh grade armed with advice his grandfather gave him--to find a thing he's good at and become the best at it. But Rahul struggles with his identity, including his confusing attraction to classmate Justin Emery. Rahul joins the Mathletes but it doesn't go as planned, and when Jenny asks him to a dance, Rahul spirals into depression and anxiety. With the help of his best friend Chelsea, Rahul confronts who he actually is.